Customer Value And Customer Satisfaction As Mediation Of Mis And Service Quality To Brand Trust And Reputation Of Private Universities In Kepulauan Riau Province - Husda, Nur Elfi (Prosiding International conference on Information Technology and Business (ICITB), 2017)
his study aims to test and analyze brand trust and reputation variables of private universities from the aspects that influence the Management Information System (MIS), service quality, customer value and customer satisfaction. Structural Equation Modeling is used to find out the conceptual model of brand trust and reputation of private universities. The population of this study are students from the study program of private university management in Kepulauan Riau Province in 2016 who have used Academic Information System and B accredited that is 3,513 students. The sample size is 360 which is distributed proportionally at each location at each private University. The results showed that the better the MIS in the college will be the better the college in students value, but good or bad the existing MIS does not determine the satisfaction or dissatisfaction of students to services provided by the university. Better service quality will make students satisfied and add good grades of college in students value. If the better the value of college for the students will further increase the students trust toward the good name of the college and improve the reputation of the college for the students. The more satisfied of student will be satisfied for the services provided will also brand of trust of the college and improve the reputation of the college. Study of brand trust and reputation of the college that is influenced by Management Information System, the quality of service with customer value mediation and customer satisfaction variables is still infrequent, so with the present research can give a positive contribution to the development of private universities and to further improve the quality of universities high private sector in producing graduates who excel and competitiveness, especially with state universities.Â KeywordS : Brand Trust, MIS, Private Universities, Service Quality, and Reputation